Participatory Action Research: a Process of Ref lection on the Pedagogical Practice - Chacón Céspedes, Melissa (2017)
This article presents a reflection on the pedagogical experience of the participatory action research process (PAR). This experience was conducted during the course on art titled Humanism, Theater, and Society, given at the General Studies Center, at the National University of Costa Rica. Through the connection of the impact of art, specifically of theater, on the university world, an integral development of the lived process is strengthened, since the purpose was to rediscover us, to recognize us, to feel ourselves, to get us reconnected to ourselves, to experience again all those abilities the institutionality has made hidden or has oppressed. It was possible to make structures visible to fight against the control and the respect through fear, derision, the banking education model, imposition, and factors experienced in the traditional educational spaces. The experience is based on Paulo Freire’s pedagogy. Arts are assumed to have multiple codes of expression. The purpose of arts is to humanize and raise awareness through diverse languages. Arts can convey messages, ideas, sensations, emotions, reflections; they have been a means to communicate, contributing to people life with multiple benefits. Despite the advantages people receive from art, this activity has had a slow development process in Costa Rica.